ANALYSIS OF ELEMENTARY SCHOOL STUDENTS' CRITICAL THINKING SKILLS IN THE SUBJECTS OF NATURAL SCIENCE AND SOCIAL STUDIES - Aini Shofiyana Dewi; Ani Rusilowati; Woro Sumarni; Abdul Mufid; Koteit Naim (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
The ability to think critically is a skill that students need to cope with the challenges of today's world. The aim of this study is to analyze the critical thinking skills of fourth-grade students in science materials at SD Islam Ummina and SDN 1 Tunjungan for the 2022/2023 academic year. This research employs a quantitative descriptive method, with data collected by providing High Order Thinking Skills (HOTS) questions with critical thinking indicators related to science material to 52 students of grade IV SD. The results of the PAP analysis on the final test showed that 7 students (13%) had high critical thinking skills, 5 students (10%) had good critical thinking skills, 18 students (35%) had sufficient critical thinking skills, and 22 students (42%) had low critical thinking skills. Furthermore, in the distribution of student answers, the minimum score was 110 with a percentage of 21% for question number 7, which utilized type C5 questions with complex multiple-choice formats. Thus, the students' ability to solve questions at levels C4, C5, and C6 is still low. Based on these results, it can be concluded that the critical thinking skills of fourth-grade students at SD Islam Ummina and SDN 1 Tunjungan are still low.